Study on Happening and Extincting Mechanism of a Squall Line along the Eastern Helan Mountain. Issue 1 (May 2021) - Wei, Li; Guoping, Hong; Jianhua, Mu; Jia, He; Jun, Yan; Hejiang, Zuo
Abstract: In the afternoon of June 17, 2020, a squall line occurred over the eastern region of Helan Mountain in Ningxia, accompanied by lightning, strong wind and short-term heavy precipitation, which affected north and middle part of Ningxia and Wuhai of Inner Mongolia. Basing on the Doppler radar data and conventional meteorological observation data, the weather process was analyzed. the results show that: (1) the cold air from the middle and high latitudes intersected with the near surface warming air in Alashan of Inner Mongolia, which promoted the development of convection and induced the formation of squall line; (2) the temperature and pressure field at high and low level were asymmetrical and the weather system presented a forward tilting structure, which was conducive to the occurrence of strong convective weathers such as squall line; (3) the squall line strengthened when moving across Helan Mountain due to the topographic uplifting and the strong vertical wind shear;(4) After moving into north and middle part of Ningxia, the convergence and divergence configuration of the squall line weakened, the circulation energy faded and the convective structure and circulation field became incomplete gradually, the inclined sinking airflow in the back of the squall line gradually weakened due to the precipitation.